2015
DOI: 10.4172/2157-7471.1000262
|View full text |Cite
|
Sign up to set email alerts
|

AFLP Fingerprinting for Identification of Infra-Species Groups of Rhizoctonia solani and Waitea circinata

Abstract: Patch diseases caused by Thanatephorus cucumeris (Frank) Donk and Waitea circinata Warcup and Talbot varieties (anamorphs: Rhizoctonia species) pose a serious threat to successful maintenance of several important turfgrass species. Reliance on field symptoms to identify Rhizoctonia causal agents can be difficult and misleading. Different Rhizoctonia species and Anastomosis Groups (AGs) vary in sensitivity to commonly applied fungicides and they also have different temperature ranges conducive for causing disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Interestingly, recognition responses previously described in geographically different F. mosseae isolates (Giovannetti et al 2003), represented by the differentiation of lateral tips in the contacted hyphae in correspondence of the approaching ones, were often detected here during contacts between different lineages' hyphae. (Amaradasa et al 2015;Cilliers et al 2000;Okabe and Matsumoto 2000). Accordingly, if we consider the F. mosseae lineages that we analyzed as belonging to a single VCG because all pairings showed hyphal fusions, it is worth comparing their genetic divergence with anastomosis ability.…”
Section: Rhizoglomus Clarus Andmentioning
confidence: 99%
“…Interestingly, recognition responses previously described in geographically different F. mosseae isolates (Giovannetti et al 2003), represented by the differentiation of lateral tips in the contacted hyphae in correspondence of the approaching ones, were often detected here during contacts between different lineages' hyphae. (Amaradasa et al 2015;Cilliers et al 2000;Okabe and Matsumoto 2000). Accordingly, if we consider the F. mosseae lineages that we analyzed as belonging to a single VCG because all pairings showed hyphal fusions, it is worth comparing their genetic divergence with anastomosis ability.…”
Section: Rhizoglomus Clarus Andmentioning
confidence: 99%
“…[ 35 , 36 , 37 , 38 , 39 , 40 ]. Genetic differences in hypertension and their subgroups have been phylogenetically assessed using PCR-based DNA fingerprint techniques even in the absence of prior knowledge of the sequences [ 34 , 41 , 42 , 43 , 44 ]. Several studies have reported that Rhizoctonia isolates within many AGs have caused diseases in important crops in Turkey to date [ 11 , 45 , 46 , 47 , 48 , 49 ]; however, there are no detailed reports identifying the AGs and their subgroups of Rhizoctonia isolates causing the root rot and wirestem of red cabbage in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although the ITS (ITS-5.8S-ITS2) primary sequences of all the three isolates of Rtul formed a well-supported clade in the phylogenetic tree (Figure 6), molecular morphometric analyses clearly differentiated them as three potentially distinct sexual species within R. tuliparum, sensu lato, per Müller et al [45] and Wolf et al [31] (Figure 8; Table S4), and call for further investigation. Moreover, from disease epidemiology and management viewpoints, our findings call for accurate identification of pathogen genotypes as well as determination of sensitivities of genetically diverse isolates of Rhizoctonia pathogens to commonly used fungicides [13,43,[47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%